The Meaning of Rahmatan Lil Alamin in the Contemporary Tafseer of Muhammad Quraish Shihab - Moch. Farich Alfani (Indonesian Academy of Social and Religious Research (IASRR), 2023)
One of the problems that occur in the Indonesian education sector is the degradation of the character of students. The results of research conducted by the Indonesian Islamic Education Study Institute (LaPPI) in 2009 were truly surprising, as many as 57.8% of students in Jabodetabek became pregnant out of wedlock and found other delinquents. Therefore, to address this problem requires benchmarks in the form of the Al-Qu'an and Hadith. In this case, by taking a study of the meaning of Rahmatan Lil Alamin in the contemporary interpretation of Shihab's work. This research obtained results by revealing that Islam plays a very big role in all cultures, especially in the education of generations of Muslim scholars so that they can prepare cadres of successors to religions and nations who have the soul problem solver, become an active contributor, and understand the contemporary Islamic world. This research uses the library research method. The data source used is the Koran and its interpretations which are used as the main data source, as well as using various literature on the book of turots and other research studies as supporting sources.